Estimation of metal state in molten production processes using electromagnetic tomography with fast integrated processing. (1st July 2022) - Chen, Ziqi; Hao, Haibin; Salas-Avila, J R; Fan, Mingyang; Xie, Yuedong; Wang, Shupei; Li, Jiyao; Xu, Jianxin; Wang, Hua; Yin, Wuliang
Abstract: This paper presents imaging of copper slag solidification processes using electromagnetic tomography (EMT). It describes key components of the measurement system including a sensor that can operate in the harsh temperature environments. An integrated process tomography system is detailed that includes the main processing unit, i.e. a field programmable gate array and other front end circuitries. It is capable of delivering a wide excitation signal frequency ranging from 0.1 Hz to 500 kHz and a fast speed of 131 frames s −1 with a typical signal-to-noise ratio of 66 dB–95 dB. Measurement trials were conducted on a molten converter slag solidification process where the copper slag changes from the molten state to solidification state during the cool-down for more than an hour. The phenomenon in which the disorderly distributed metal gradually forms solid and permeable object was observed, which can indicate the status of the process. This is the first report of observing such a process using an EMT system. Moreover location-based convergence analysis has been carried out in the imaging space and useful new insights have been gained for the copper production process, which would be difficult to obtain otherwise. Verification and calibration using x-ray diffraction and scanning electron microscope indicate the viability of the EMT-based measurement method.